Conducting the Heavenly Chorus: Constituent Contact and Provoked Petitioning in Congress. Issue 1 (25th March 2023) - Henderson, Geoffrey; Hertel-Fernandez, Alexander; Mildenberger, Matto; Stokes, Leah C.
Abstract : Congress hears more and more from everyday citizens. How do modern Congressional offices use this information to represent their constituents? Drawing on original interviews and a survey of Congressional staff, we explore how representation works in practice when new data and tools, such as databases and downscaled public opinion polls, are available. In contrast with established theories that focus on responsiveness, we show that representation is a two-way street. Congressional offices both respond to incoming constituent opinion and reach out to elicit opinions from stakeholders. Offices record correspondence into databases, identifying the most salient issues and the balance of opinion among correspondents. They tend not to use polls on policy. To understand the opinions of electorally influential constituencies, staffers also proactively reach out to stakeholders and experts in a practice we call provoked petitioning. If the Washington pressure system is a chorus, Congressional staff often serve as conductors, allowing well-resourced and organized constituents, including interest groups, to sing with the loudest voices. While Congress has some new tools and strategies for representation, its modern practices still reinforce existing biases.